EV‐Elute: A universal platform for the enrichment of functional surface marker‐defined extracellular vesicle subpopulations - Willemijn S. deVoogt; Rowan Frunt; Raul M. Leandro; Casper S. Triesscheijn; Bella Monica; Ioanna Paspali; Mark Tielemans; Jerney J. J. M. François; Cor W. Seinen; Olivier G. deJong; Sander A. A. Kooijmans (Journal of Extracellular Vesicles)
Abstract Intercellular communication via extracellular vesicles (EVs) has been identified as a vital component of a steadily expanding number of physiological and pathological processes. To accommodate these roles, EVs have highly heterogeneous molecular compositions. Given that surface molecules on EVs determine their interactions with their environment, EV functionality likely differs between subpopulations with varying surface compositions. However, it has been technically challenging to examine such functional heterogeneity due to a lack of non‐destructive methods to separate EV subpopulations based on their surface markers. Here, we used the Design‐of‐Experiments (DoE) methodology to optimize a protocol, which we name ‘EV‐Elute’, to elute intact EVs from commercially available Protein G‐coated magnetic beads. We captured EVs from various cell types on these beads using antibodies against CD9, CD63, CD81 and a custom‐made protein binding phosphatidylserine (PS). When applying EV‐Elute, over 70% of bound EVs could be recovered from the beads in a pH‐ and incubation‐time‐dependent fashion. EV subpopulations showed intact integrity by electron microscopy and Proteinase K protection assays and showed uptake patterns similar to whole EV isolates in co‐cultures of peripheral blood mononuclear cells (PBMCs) and endothelial cells. However, in Cas9/sgRNA delivery assays, CD63+ EVs showed a lower capacity to functionally deliver cargo as compared to CD9+, CD81+ and PS+ EVs. Taken together, we developed a novel, easy‐to‐use platform to isolate and functionally compare surface marker‐defined EV subpopulations. This platform does not require specialized equipment or reagents and is universally applicable to any capturing antibody and EV source. Hence, EV‐Elute can open new opportunities to study EV functionality at the subpopulation level.